A highly-sensitive flexible tactile sensor array utilizing piezoresistive carbon nanotube–polydimethylsiloxane composite. (11th July 2018) - Sun, Xuguang; Wang, Chunkai; Chi, Cheng; Xue, Ning; Liu, Chang
Abstract: This paper reports on a 6  ×  8 flexible piezoresistive tactile sensor array composed of a multi-walled carbon nanotube (MWCNT)–polydimethylsiloxane (PDMS) composite. The sensor array has properties such as high flexibility, stretchability, uniformity and sensitivity, contributing to the anomalous-shaped surface nano-composite structure on the sensing elements. The sensitivity of the tactile sensor is 16.9–5.41 in a low-pressure range (<300 Pa) and  >0.5 at 1.3 kPa for the 125 µ m thick composite sensing materials. The systematic study of the pressure response of the developed tactile sensor array in terms of various composite thickness, temperature, uniformity and repeatability have been conducted. Moreover, an array scanning system has been established and the applied pressure was detected, digitalized and displayed in real-time. This work has high potential for low-range pressure detection and artificial skin applications.